Answer:
![x=-(7)/(6)\\x=(1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wrdorcqukhstv97tgpabm2hn8e7slu0j8u.png)
Explanation:
The equation to solve is:
![(x+(1)/(2))^2=(4)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tkta61hp5nq813lszxaflc56jaikcc84b1.png)
To get rid of the "square", we need to take square root of both sides:
![\sqrt{(x+(1)/(2))^2}=\sqrt{(4)/(9)}\\x+(1)/(2)=(√(4))/(√(9))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aonondvwkgdi19qvnxpxjtnb8m9hld4lyo.png)
Then we use algebra to find the value(s) of x. Remember, when we take square root, we have to add up a "+-" (on the right side). Shown below:
![x+(1)/(2)=+-(√(4))/(√(9))\\x+(1)/(2)=+-(2)/(3)\\x=(2)/(3)-(1)/(2)=(1)/(6)\\x=-(2)/(3)-(1)/(2)=-(7)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hjep9lhwn08jyjl3nsa1iek8mh2c9z8ti9.png)
So these are 2 answers for x.